2018 25th Asia-Pacific Software Engineering Conference (APSEC) 2018
DOI: 10.1109/apsec.2018.00046
|View full text |Cite
|
Sign up to set email alerts
|

Are Smell-Based Metrics Actually Useful in Effort-Aware Structural Change-Proneness Prediction? An Empirical Study

Abstract: Bad code smells (also named as code smells) are symptoms of poor design choices in implementation. Existing studies empirically confirmed that the presence of code smells increases the likelihood of subsequent changes (i.e., changeproness). However, to the best of our knowledge, no prior studies have leveraged smell-based metrics to predict particular change type (i.e., structural changes). Moreover, when evaluating the effectiveness of smell-based metrics in structural change-proneness prediction, none of exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…They recommended adopting the class size indicator as a confounding variable when constructing a model based on object‐oriented metrics. Liu et al 51 studied the correlation between code smell and change‐proneness. Their results demonstrated that programs with code smell are more likely to be modified, and that the performance of the change prediction model based on code smell is better than one based on CK measurements.…”
Section: Related Workmentioning
confidence: 99%
“…They recommended adopting the class size indicator as a confounding variable when constructing a model based on object‐oriented metrics. Liu et al 51 studied the correlation between code smell and change‐proneness. Their results demonstrated that programs with code smell are more likely to be modified, and that the performance of the change prediction model based on code smell is better than one based on CK measurements.…”
Section: Related Workmentioning
confidence: 99%